Combination of t(t)over-bar cross section measurements and constraints on the mass of the top quark and its decays into charged Higgs bosons - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Bertram, I.; et al. (Amer Physical Soc, 2009)
We combine measurements of the top quark pair production cross section in p (p) over bar collisions in the l + jets, ll, and tau l final states ( where l is an electron or muon) at a center of mass energy of root s = 1.96 TeV in 1 fb(-1) of data collected with the D0 detector. For a top quark mass of 170 GeV/c(2), we obtain sigma(t (t) over bar) = 8.18(-0.87)(+0.98) pb in agreement with the theoretical prediction. Based on predictions from higher order quantum chromodynamics, we extract a mass for the top quark from the combined t (t) over bar cross section, consistent with the world average of the top quark mass. In addition, the ratios of t (t) over bar cross sections in different final states are used to set upper limits on the branching fractions B(t -> H(+)b -> tau(+) vb) and B(t -> H(+)b -> c (s) over barb) as a function of the charged Higgs boson mass.